The Influence of Financial Literacy, Trust, User Innovation on MSMEs’S Fintech Adoption in Sampang Regency - amaniyah, evaliati; Aguilika, Deykha (Trunojoyo University of Madura, 2025)
This study aims to determine the adoption of fintech by MSMEs in Sampang Regency by testing the impact of financial literacy, trust and user innovation on fintech adoption. The study was conducted on MSMEs in Sampang Regency who use financial technology. The analysis used multiple linear regression with PLS. The results of this study indicate that financial literacy and trust have no effect on fintech adoption. However, user innovation has a positive effect on fintech adoption. These findings can be a useful reference to increase insight and direction to help design digital financial education and literacy programs, especially for MSMEs.